Heparin-binding epidermal growth factor-like growth factor (HB-EGF) protected intestinal ischemia-reperfusion injury through JNK and p38/MAPK-dependent pathway for anti-apoptosis - Yung-Ching Ming; Hsun-Chin Chao; Shih-Ming Chu; Chih-Cheng Luo (Elsevier, 2019)
Background: Heparin-Binding Epidermal Growth Factor-Like Growth Factor (HB-EGF) is a potent cytoprotective factor in various body systems, including gastrointestinal tract. In this study, we intended to examine whether HB-EGF exerts its protective effects through MAPK dependent anti-apoptosis after intestinal I/R injury. Methods: We randomly divided 30 laboratory 30 rats into 5 groups: (A) normal control group, (B) ischemia group with normal saline, (C) I/R group with normal saline, (D) ischemia group with HB-EGF (400 ug/kg), and (E) I/R group with HB-EGF (400 ug/kg). With Western blotting study, we determined JNK and p38/MAPK pathway and caspase-3 activity protein levels using Western analyses. Results: The JNK phosphorylation protein levels increased after intestinal ischemia or intestinal reperfusion phase, and HB-EGF pre-treatment was significantly decreased in JNK phosphorylation protein levels (p < 0.01). We found that p38 protein levels was increased after intestinal reperfusion phase, and that HB-EGF pre-treatment significantly decreased p38 protein levels (p < 0.01). The expression protein level of caspase 3 was increased after intestinal ischemia or intestinal reperfusion phase. HB-EGF pre-treatment significantly decreased Caspase 3 proteins. (p < 0.01). Conclusion: Our study revealed that pre-treatment of HB-EGF decreased the amount of activity of JNK and p38/MAPK pathway and caspase-3 protein after intestinal I/R injury. These results may further support that the cytoprotective of HB-EGF after I/R injury could be through anti-apoptotic effect of activity of JNK and p38/MAPK pathway. Key Words: anti-apoptotic effects, HB-EGF, intestinal I/R injury, JNK, p38/MAPK